Effects of infection with Anguillicola crassus and simultaneous exposure with Cd and 3,3′,4,4′,5-pentachlorobiphenyl (PCB 126) on the levels of cortisol and glucose in European eel (Anguilla anguilla) - Sures, B.; Lutz, I.; Kloas, W. (Parasitology, 2005)
This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively. To investigate whether the stress response of European eels infected with Anguillicola crassus is influenced by environmental pollutants, experimentally infected eels were exposed to Cd and/or to 3,3′, 4,4′, 5-pentachlorobiphenyl (PCB 126). Serum cortisol and glucose concentrations of these eels were monitored over a period of 103 days and were compared with data from infected, unexposed eels as well as with data from uninfected eels. Additionally, the levels of cortisol were correlated with concentrations of Anguillicola-specific antibodies. All eels showed an initial increase of the cortisol levels until day 63. This general elevation of plasma cortisol is most likely due to handling stress, as all eels were repeatedly netted and afterwards inoculated with a feeding tube. At the end of the exposure period eels which were infected and those which were infected and simultaneously exposed to Cd and PCB showed significantly higher levels than the controls. The general course of serum glucose levels in eels resembled that of cortisol. Accordingly, Spearman correlation analysis revealed that an increase in serum cortisol concentrations is correlated with rising levels of glucose. With respect to immune-endocrine interactions a significant negative correlation between cortisol and anti-A. crassus antibodies was found. Our data show that A. crassus is the most potent stressor for European eels among the treatments tested within this study. This is important in terms of ecotoxicological studies as the main effects are caused by parasites rather than chemicals. Accordingly, effects of parasites on the physiological homeostasis of organisms must be considered in ecotoxicology. From the parasitological point of view our results suggest that probably as part of an unbalanced host-parasite interaction A. crassus evokes a strong cortisol ...